2021
DOI: 10.34172/apb.2022.040
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Apatinib in Combination with Piperine on MDM-2 Gene Expression, Glutathione Peroxidase Activity and Nitric Oxide level as Mechanisms of Cytotoxicity in Colorectal Cancer Cells

Abstract: Purpose: Apatinib has been utilized in colon cancer therapies but its efficiency and molecular mechanism are not fully understood. Chemotherapy in combination with non-toxic compounds can be a strategy to reduce the recurrence of cancer. Consequently, this study was carried out to evaluate the effects of Apatinib and Piperine on colorectal cancer (CRC) cell line and their potential anti-cancerous mechanisms in vitro. Methods: The effects of Apatinib and Piperine on HCT-116 CRC cells were detected by assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this study, we showed that lncRNA DHRS4-AS1 acts as a scaffold to enhance interactions between the E3 ligase MDM2 and DHX9. MDM2 serves as E3 Ligase regulates cancer cell proliferation in various tumors [ 40 ]. DHRS4-AS1 directly binds to DHX9 and negatively regulates DHX9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that lncRNA DHRS4-AS1 acts as a scaffold to enhance interactions between the E3 ligase MDM2 and DHX9. MDM2 serves as E3 Ligase regulates cancer cell proliferation in various tumors [ 40 ]. DHRS4-AS1 directly binds to DHX9 and negatively regulates DHX9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines, in particular, have been in the spotlight as a viable alternative to conventional medical care due to the high cost of conventional medicine and the inability of various countries to provide essential medicines. Herbal medicines are also culturally acceptable to people and have good efficacy, safety, low toxicity, and minimal environmental pollution [ 8 , 12 15 ]. More emphasis should be placed on the fact that integrating herbal medications into conventional medical practices is hampered by the absence of clinical and pharmacological data for most herbal medicinal products [ 16 ].…”
Section: Introductionmentioning
confidence: 99%